miR-383-3p and miR-6951-3p activate cell proliferation through the regulation of genes related to hypertelorism - Iwaya, Chihiro; Iwata, Junichi (Frontiers in Cell and Developmental Biology, 2025)
Hypertelorism, characterized by an abnormal increase in the distance between the eyes, is often associated with various congenital birth defects. While there is increasing evidence suggesting common underlying mechanisms for hypertelorism, the role of microRNAs (miRNAs)—short noncoding RNAs that suppress target genes by inhibiting translation and degrading mRNA—in the condition’s pathogenesis remains unclear. This study aimed to identify the miRNAs associated with hypertelorism in mice. By searching the Mouse Genome Informatics (MGI) database and reviewing full-text references, we identified a total of 31 genes potentially related to hypertelorism. Advanced bioinformatics analyses revealed nine miRNAs that may regulate these genes. We experimentally evaluated candidate miRNAs in assays of cell proliferation and target gene regulation in primary cells isolated from developing frontonasal process mouse embryonic frontonasal mesenchymal and O9-1 cells, a murine neural crest cell line. Our findings indicated that overexpression of either miR-383-3p or miR-6951-3p stimulated cell proliferation, whereas miR-7116-3p and miR-124-3p did not have this effect. Additionally, we confirmed that miR-383-3p and miR-6951-3p regulated the expression of a set of hypertelorism-related genes in a dose-dependent manner. These results suggest that miR-383-3p and miR-6951-3p play significant roles in the development of hypertelorism.